Bacterial Community Dynamics and Biocement Formation during Stimulation and Augmentation: Implications for Soil Consolidation - Dhami, Navdeep K.; Alsubhi, Walaa R.; Watkin, Elizabeth; Mukherjee, Abhijit (Frontiers in Microbiology, 2017)
Microbially-induced CaCO3 precipitation (MICP) is a naturally occurring process wherein durable carbonates are formed as a result of microbial metabolic activities. In recent years, MICP technology has been widely harnessed for applications in civil engineering wherein synthesis of calcium carbonate crystals occurs at ambient temperature paving way for low energy biocement. MICP using pure urease (UA) and carbonic anhydrase (CA) producing bacteria has been promising in laboratory conditions. In the current study we enriched ureolytic and carbonic anhydrase communities in calcareous soil under biostimulation and bioaugmentation conditions and investigated the effect of microbial dynamics on carbonate precipitation, calcium carbonate polymorph selection and consolidation of biological sand column under nutrient limited and rich conditions. All treatments for stimulation and augmentation led to significant changes in the composition of indigenous bacterial population. Biostimulation as well as augmentation through the UA route was found to be faster and more effective compared to the CA route in terms of extracellular enzyme production and carbonate precipitation. Synergistic role of augmented cultures along with indigenous communities was recorded via both the routes of UA and CA as more effective calcification was seen in case of augmentation compared to stimulation. The survival of supplemented isolates in presence of indigenous bacterial communities was confirmed through sequencing of total diversity and it was seen that both UA and CA isolate had the potential to survive along with native communities under high nutrient conditions. Nutrient conditions played significant role in determining calcium carbonate polymorph fate as calcitic crystals dominated under high carbon supplementation. Finally, the consolidation of sand columns via stimulation and augmentation was successfully achieved through both UA and CA route under high nutrient conditions but higher consolidation in short time period was noticed in UA route. The study reports that based upon the organic carbon content in native soils, stimulation can be favoured at sites with high organic carbon content while augmentation with repeated injections of nutrients can be applied on poor nutrient soils via different enrichment routes of microbial metabolism.